UNIVERSITY INNOVATION INFRASTRUCTURE MODEL AS A KEY PART OF A TERRITORAL CLUST - Nataliya P. Ivashchenko; Tatiana V. Pospelova; Alexandra A. Engovatova (Модернизация, инновация, развитие)
Over the recent decades there have been increasing efforts by developing countries to reduce the economic gap between developed and developing countries. Asian and Northern European countries demonstrate good progress in these areas.Sweden,Denmark,Chinashow stable high economic indicators that have been achieved by targeted government programs. These programs were aimed at creating a new type of economy based on knowledge and new technologies. Given the success of these countries, a number of developing countries, whose economies are dependent on resources, today, are looking to repeat their way; those countries areRussia,Indonesia,BrazilandChile. The modernization of the economy and the formation of innovative economy are key objectives of the state policies of these countries. The research by leading economists and scientists led to the conclusion that the regional level of national economy plays a key role in formation of knowledgebase economy, which indicates the need to differentiate the innovation policy of the state depending on the economy parameters of each region. This paper presents a model of the first stage of the formation of the entrepreneurialuniversityUniversityinnovation infrastructure model, which is a key part of a territoral cluster. The article consists of five parts. The first part covers the analysis of the two main models of regional development: clustering theory and Triple Helix. This section describes a positive result, which is achieved by using these models simultaneously. The second part of the article shows the importance and the role of the entrepreneurial university in the formation of innovative clusters. It will be explained how and under what conditions this formation is achieved. The third part of this paper will present University innovation infrastructure model. The fourth part will examine the practical first steps to create a cluster "Vorob’evi Gori" on the basis of theMoscowStateUniversity. The fifth, final part contains the main conclusions of the article and the next steps in the investigation of this subject.